1995
DOI: 10.1093/jnci/87.11.836
|View full text |Cite
|
Sign up to set email alerts
|

Mutagens From Heated Chinese and U.S. Cooking Oils

Abstract: The common use of wok cooking in China might be an important but controllable risk factor in the etiology of lung cancer. In the United States, where cooking oils are usually refined for purity, additional studies should be conducted to further quantify the potential risks of such methods of cooking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(99 citation statements)
references
References 0 publications
5
92
1
Order By: Relevance
“…Oil temperature is normally around 240 -2701C during deep-frying. It has been reported that deep-frying also generates fumes containing mutagenic compounds (de Meester and Gerber, 1995;Shields et al, 1995). These mutagens or carcinogens have been linked to an increased risk of cancers among Western populations (Zimmerli et al, 2001;Sinha et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Oil temperature is normally around 240 -2701C during deep-frying. It has been reported that deep-frying also generates fumes containing mutagenic compounds (de Meester and Gerber, 1995;Shields et al, 1995). These mutagens or carcinogens have been linked to an increased risk of cancers among Western populations (Zimmerli et al, 2001;Sinha et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological findings indicate that emission of acrolein from wok cooking rather than tobacco smoking is linked to the high incidence of lung cancer in Chinese women [31]. A study conducted by Shields and co-workers [32] determined the acrolein emissions from wok cooking to be highest for unrefined Chinese rapeseed oil and lowest for peanut oil. Acrolein emissions were reduced at lower temperatures, as expected, but also reduced when the antioxidant butylated hydroxyanisole was added to the cooking oil, suggesting that lipid peroxidation processes are involved in the formation of acrolein.…”
Section: Lipids As a Source Of Acroleinmentioning
confidence: 99%
“…Cigarette smoke is another important source of Acr with concentrations up to 300 μg/l in mainstream smoke [7,8]. High temperature cooking of oils generates Acr as a major product [9]. Because of widespread exposure and potential harmful effects to humans, Acr is one of the most studied pollutants.…”
Section: Introductionmentioning
confidence: 99%